The politics of local participatory democracy in Latin America : institutions, actors, and interactions - Montambeault, Françoise (Stanford University Press, 2015)
Participatory democracy innovations aimed at bringing citizens back into local governance processes are now at the core of the international democratic development agenda. Municipalities around the world have adopted local participatory mechanisms of various types in the last two decades, including participatory budgeting, the flagship Brazilian program, and participatory planning, as it is the case in several Mexican municipalities. Yet, institutionalized participatory mechanisms have had mixed results in practice at the municipal level. So why and how does success vary? This book sets out to answer that question.